Stakeholder mapping for climate change action in Tajikistan - Babu, Suresh Chandra; Tohirzoda, Sino; Srivastava, Nandita (International Food Policy Research Institute, 2024)
Central Asia is highly vulnerable to climate change threats, which have negatively impacted both humans and wildlife. Tajikistan, one of the least urbanized countries in the region, is prone to natural disasters, disruptions in rainfall, growing temperatures, reductions in glacial cover, and extreme weather events (Zoï Environment Network 2020; Green Climate Fund [GCF] 2020). The Government of the Republic of Tajikistan acknowledges the problems and risks posed by climate change and is working toward ad dressing them to meet the United Nations (UN) Sustainable Development Goals (SDGs) focused on climate change and environmental concerns. One critical step in this direction is the submission of its updated Nationally Determined Contributions (NDCs) in 2021, which states the country’s proposed efforts to support sustainable and efficient development, taking into consideration climate change, environmen tal, and socioeconomic challenges for the period 2020–2030 (Government of the Republic of Tajikistan 2021). Weak institutional capacity and lack of efficient vertical and horizontal coordination between mul tiple stakeholders could undermine the possibility of undertaking integrated climate change actions, how ever. Thus, given the interconnected and multistakeholder nature of climate change issues, the first step is to identify all relevant stakeholders. This effort must be accompanied by an understanding of how the country’s multisectoral climate change issues are being addressed through the policy system and na tional and regional institutions and how development partners support these efforts (Clar and Steurer 2019). In this paper, we map institutions, stakeholders, and relevant policies that support NDC implementa tion in Tajikistan and understand their specific roles and responsibilities and related interlinkages. The key impact objective of this paper is to create a knowledge product that helps strengthen vertical and horizontal coordination between institutions working on climate change issues in Tajikistan.